(untitled) (Bangladesh Critical Care Journal, 2019)
Background: Soft tissue mass in gall bladder (GB) is a radiologic finding commonly encountered in surgical practice. It needs proper evaluation as there is a fair chance that it can be a malignant lesion. Gall bladder cancer (GBC) is considered an incurable disease with an extremely poor prognosis. However, there is good chance of survival if it can be diagnosed in earlier stages (stage Ib, II, selective III). Methods: All consecutive cases of soft tissue mass lesions of GB found in ultrasonogram of abdomen and admitted in Hepato-Biliary-Pancreatic Surgery (HBPS) unit of BIRDEM hospital, from January 2009- September 2016, were included in this study. Detailed history and thorough clinical examination was done in all cases. Pre-operative evaluations were done by ultrasound, Tumor marker (CA19.9) & CT scan,. CT scan was a crucial investigation for all the patients, as depending on the findings, decision was made whether a patient is eligible for a possible curative surgery or not. On-table frozen section biopsy or imprint cytology was done for tissue diagnosis. Radical resection was done for the histology/ cytology proved malignancy of gallbladder (stage Ib, II, selective III). Post-cholecystectomy patients also underwent full thickness excision of the umbilical port. In benign cases only cholecystectomy was done. Advanced GBC cases underwent FNAC for tissue diagnosis followed by palliative chemotherapy. Some needed endoscopic or surgical palliation in the form of percutaneous external biliary drainage, endobiliary prosthesis, triple bypass, hepaticojejunostomy, left duct anastomosis, gastrojejunostomy, ileotransverse anastomosis, external biliary drainage etc before chemotherapy. All the GBC patients were regularly followed according to a schedule. Results: We are reporting 334 cases of soft tissue mass lesions of GB. Female 191 (57.2%) and male 143 (42.81%), M : F = 1 : 1.3 , between the ages of 32 and 88 years. Of these, 81 patients (24.2%) turned out to be benign; another 81 patients (24.2%) were in early stage (Ib, II selective III). The rest of 172 patients (51.5%) showed signs of advanced malignancy in USG & CT scan. Post-operative complications occurred in 27 cases (8.1%). During follow-up, 34 patients (42%) have crossed their 5 years of disease free survival after curative surgery. Rest of the patients (44 cases), after curative surgery, are still under follow-up. The 172 patients in Stage III & IV disease who underwent some sort of palliative procedure, had a mean survival of 7.2 months. Conclusion: Soft tissue mass in gall bladder picked up by imaging has a very high chance to be malignant. Among these malignant patients, a good number has a chance of curative resection if evaluated and managed properly. Bangladesh Crit Care J March 2019; 7(1): 29-34